Management and outcomes in critically ill nonagenarian versus octogenarian patients - Bruno, Raphael Romano (2021)
Funding Information: This study was endorsed by the ESICM. Free support for running the electronic database and was granted from the dep. of Epidemiology, University of Aarhus, Denmark. Financial support for creation of the e-CRF and maintenance of the database was possible from a grant (open project support) by Western Health region in Norway) 2018 who also funded the participating Norwegian ICUs. DRC Ile de France and URC Est helped conducting VIP2 in France. Open Access funding enabled and organized by Projekt DEAL. Publisher Copyright: © 2021, The Author(s).